A FORWARD LOOKING STATEMENT OF FINANCIAL POSITION. - Ashburne, Jim G. (The Accounting Review, 1962)
Abstract The statement of financial position describes the ship and its hardware, the amount of fuel on board, and a measure of the weight to be supported in flight. It gives no run down on management skill, but it does indicate the readiness of the vehicle which they will pilot. Management's primary task in an enterprise is to make optimum use of the funds at their disposal. This activity is most readily understood when it is thought of as a process of spending cash for something which ultimately brings back a greater amount of cash. The cash-to-cash cycle is the pattern against which all transaction cycle variations are referred. The fact that some cash investments, or expenditures, are not directly reconverted to cash is common experience. Everybody recognizes cash owned, cash expected, and cash owed. The dynamic nature of the statement of financial position has been obscured by a lethargic perpetuation of an inherited format and name. Liquidation cycles have priority to investment cycles on realized cash because of contracted or legal obligations. Hence, amounts of cash required to liquidate liabilities are reported in order of maturity.